The Activity of Adenosine Deaminase in Pregnant Women with Elevated Fibrinogen Levels Caused by Hormonal Disorders (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Adenosine deaminase (ADA) is an essential enzyme within the purine salvage pathway, responsible for the irreversible deamination of adenosine and 2'-deoxyadenosine to inosine and 2'-deoxyinosine. In humans, ADA is represented by two genetically and catalytically distinct isoenzymes: ADA1 and ADA2. The isoenzyme ADA2 is a secreted protein produced by activated monocytes/macrophages and dendritic cells. Normal pregnancy is typically associated with a suppressed cellular immune response in the third trimester, accompanied by alterations in the blood plasma activity of the ADA2 isoenzyme. The literature presents conflicting data on this matter; while some studies have reported decreased ADA2 activity in pregnancy compared to non-pregnant women, other findings suggest an increase in activity. In our current study, we observed an elevation (p>0.05) of ADA2 activity in normal pregnancies (n=35, 10.05±0.593 U/L) when compared to non-pregnant controls (n=20, 8.70±0.589 U/L). However, pregnancies complicated by hormonal imbalances and elevated fibrinogen levels exhibited a significant decrease in ADA2 activity in the first trimester (6.737±0.307 U/L) compared to normal levels (9.218±0.508 U/L, p
Keywords: adenosine deaminase; fibrinogen; pregnancy; biomarker